SIFAT MEKANIK DAN OPTIK KACA SENG MAGNESIUM FOSFAT - Eko Budiyanto; Agus Setyo Budi; Erfan Handoko; Md. Rahim Sahar (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Glass ZnO-MgO-P2O5 with the addition of ZnO composition between 0-15 mol% has been successfully using techniques Melt Quenching. With the analysis of X-ray diffraction (XRD) structure of glass obtained showed properties of amorphous materials. Photoluminescence spectrum has a dominant emission band on the observation of the peak at around 385nm. Sedangjkan hardness test of glass ZnO-MgO-P2O5 decreased with the increasing composition of ZnO. Keywords: glass ZnO-MgO-P2O5; photoluminescence spectrum; melt quenching; XRD; hardness test.